Pemanfaatan Media Interaktif Sebagai Sarana Pembelajaran Efektif Di Era Digital - Mailizar; Ghina Annisa; Yuan Andinny (AMMA : Jurnal Pengabdian Masyarakat, 2025)
The rapid development of digital technology has a significant impact on various aspects of life, including the world of education. In this digital era, conventional learning methods that only rely on face-to-face delivery of materials and the use of textbooks as the main source are considered less effective to meet the increasingly dynamic learning needs of students. The current generation, often referred to as "digital natives," has different learning tendencies than previous generations. They are more familiar with technology, prefer visualization, and have shorter attention spans. Therefore, innovation in learning methods is needed to increase student interest, understanding, and participation. One of the innovations that can be implemented is the use of interactive media in learning. Interactive media such as learning applications, educational videos, digital simulations, and educational games have proven to be able to provide a more engaging and effective learning experience. This medium not only helps in the delivery of material in a more visual and interactive manner but also allows students to learn independently according to their own pace. In addition, interactive media allows collaboration between students as well as access to wider information, which can enhance students' understanding and creativity.